2023
DOI: 10.1002/chem.202203480
|View full text |Cite
|
Sign up to set email alerts
|

Tweezer‐Based C−H Oxidation Catalysts Overriding the Intrinsic Reactivity of Aliphatic Ammonium Substrates

Abstract: The site‐selective C−H oxygenation of alkyl chains as well as deactivated positions remains a great challenge for chemists. Here, we report the synthesis and application of four new supramolecular tweezer‐based oxidation catalysts. They consist of the well‐explored M(pdp/mcp) oxidation moiety and a molecular tweezer capable of binding ammonium salts. All catalysts display preferential oxidation of the strongly deactivated C3/C4 positions, however to different degrees. Furthermore, the best performing catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 105 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Such selectivities are higher than those previously obtained with singly bound alkyl chain monoamines (up to 81% selectivity for the two favoured methylenes). 10,11 Under oxidation conditions, catalyst Mn( CR pdp) is expected to be almost fully saturated (>98%) with both diammonium S1 and monoammonium guests. Hence, the increased selectivity observed with diammonium S1 can be ascribed to an improved pre-organization of the catalyst–substrate adduct that arises from the higher rigidity associated with the two-point binding of S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such selectivities are higher than those previously obtained with singly bound alkyl chain monoamines (up to 81% selectivity for the two favoured methylenes). 10,11 Under oxidation conditions, catalyst Mn( CR pdp) is expected to be almost fully saturated (>98%) with both diammonium S1 and monoammonium guests. Hence, the increased selectivity observed with diammonium S1 can be ascribed to an improved pre-organization of the catalyst–substrate adduct that arises from the higher rigidity associated with the two-point binding of S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Pioneering examples of the use of supramolecular receptors to govern site-selectivity in C–H oxidation have been described by Breslow, 7 and more recently by Crabtree and Brudvig, 8 Bach 9 and Tiefenbacher. 10…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this approach are most frequently based on completely covalent catalysts. Worth to mention are the site-selective CÀ H oxidation catalysts developed by Di Olivo, Di Stefano and Costas [8] and more recently by Tiefenbacher [9] in which substrate recognition and positioning occurs via binding of an ammonium terminal unit with crown ethers or cucurbiturils, respectively. Examples of specific site selectivity are interpreted as the consequence of the space and the environment inside the nanometric container.…”
Section: Introductionmentioning
confidence: 99%
“…This elegant strategy pioneered by Breslow was applied to the site-selective oxidation of C–H bonds . Particularly, recent contributions from the groups of Costas and Tiefenbacher demonstrated that supramolecular complexes can be designed for the catalyst-controlled selective oxidation of linear alkyl chains . A similar supramolecular approach was used to address the issue of enantioselectivity in intermolecular C­(sp 3 )–H amination reactions .…”
Section: Introductionmentioning
confidence: 99%